Chapter Mercury concentrations and transfers in phyto- and zooplankton communities in a coastal Mediterranean ecosystem (bay of Toulon, France) - Drouet, Flora (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Plankton is critical in contaminants transfer but its role in mercury's is to be investigated. The objective was to characterize the plankton continuum's taxonomy, trophic organization and mercury levels. Bacteria, pico-, nano- and zooplankton were more abundant in the LiB and phytoplankton in the LaB. Mercury levels were higher in the LiB. Contrarily to standard mercury biomagnification pattern in higher trophic levels, the smaller size classes presented higher mercury concentrations decreasing while size increased followed by an inversion of the trend between the two largest size classes.